Pharmacological characterization of the histamine uptake system in HL-60 human promyelocytic leukemia cells. Issue 4 (April 1986) - Gespach, Christian; Marrec, Noel; Abita, Jean-Pierre
Abstract : Serotonin and histamine H1, H2 receptor agonists or antagonists inhibited [ 3 H]histamine uptake by HL-60 cells, according to the following order of potency: impromidine >4-MH>histamine>AET>PEA and: cimetidine, histamine>diphenhydramine, serotonin. It is concluded that histamine uptake by HL-60 cells was specifically controlled by the H2 type histamine receptor and that this active process might be involved in pathophysiological regulations in leukemic and normal granulocytic precursors and in the control of histamine levels in peripheral blood and tissues in man.